2020
DOI: 10.1017/wsc.2020.79
|View full text |Cite
|
Sign up to set email alerts
|

Seed-shattering phenology at soybean harvest of economically important weeds in multiple regions of the United States. Part 2: Grass species

Abstract: Seed shatter is an important weediness trait on which the efficacy of harvest weed seed control (HWSC) depends. The level of seed shatter in a species is likely influenced by agroecological and environmental factors. In 2016 and 2017, we assessed seed shatter of eight economically important grass weed species in soybean [Glycine max (L.) Merr.] from crop physiological maturity to four weeks after maturity at multiple sites spread across eleven states in the southern, northern, and mid-Atlantic U.S. From soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…For most species, the significant negative slope relationship, regardless of weed type, showed that plants with smaller relative biomass shattered more seeds than larger plants (Table 2). This was more apparent for the grass species, possibly because these species shatter their seeds earlier in the season than the broadleaf weeds (Schwartz-Lazaro et al 2021b). Moreover, it has been reported that weed seed shatter varies across climatic conditions and agroecosystems, which was also apparent in this experiment (Taghizadeh et al 2012).…”
Section: Weed Sciencementioning
confidence: 99%
See 3 more Smart Citations
“…For most species, the significant negative slope relationship, regardless of weed type, showed that plants with smaller relative biomass shattered more seeds than larger plants (Table 2). This was more apparent for the grass species, possibly because these species shatter their seeds earlier in the season than the broadleaf weeds (Schwartz-Lazaro et al 2021b). Moreover, it has been reported that weed seed shatter varies across climatic conditions and agroecosystems, which was also apparent in this experiment (Taghizadeh et al 2012).…”
Section: Weed Sciencementioning
confidence: 99%
“…These field studies investigated the potential for HWSC to be implemented across several major crop-producing regions in the US as an additional IWM tool (Schwartz-Lazaro et al 2021a, 2021b. In general, annual broadleaf weeds are better suited to HWSC, based on the fact that these species retain their seeds for longer into the season in comparison to the annual grasses.…”
Section: Weed Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…For example, weed seed retention was greater than 90% for Palmer amaranth, smooth pigweed (Amaranthus hybridus L.), common lambsquarters (Chenopodium album L.), jimsonweed (Datura stramonium), common cocklebur (Xanthium strumarium L.), and johnsongrass up to 3 weeks after soybean maturity across the majority of states (Schwartz-Lazaro et al, 2021a). Barnyardgrass and junglerice (Echinochloa colona L.) also retained greater than 80% of seed up to 2 weeks after soybean maturity (Schwartz-Lazaro et al, 2021b). Modeling studies (Shergill et al, 2020) report greater than 80% seed retention is needed for HWSC to be viable.…”
Section: Introductionmentioning
confidence: 99%